Rancang ulang alat pengering kakao tipe drawer dryer pada usaha mandiri kakao Desa Wiyono Kabupaten Pesawaran - Risano, Yudi Eka; Tanti, Novri; Paska W, Andreas (TURBO [Tulisan Riset Berbasis Online], 2020)
Cocoa is a commodity that has a high economic value. According to the 2013 FAO, Indonesia ranks third as the largest cocoa producing country in the world and accounts for 17% of world cocoa production with an area of 1,774,303.97 ha of plantations. In Lampung province, many cocoa farmers process their own garden products into dry cocoa using conventional processes and the results are judged to be less efficient so that the quality of the dried cocoa beans produced is not good. In the conventional drying process requires firewood up to 1 cubic, drying time is 10 hours, and cocoa must be stirred every 30 minutes. This study aims to redesign conventional cocoa dryers in one of Wiyono village's independent businesses to be better in terms of heat distribution, fuel consumption, and drying time. In this research, MATLAB computation and simulation software are used to simplify the design process. The design that was carried out only modified the existing dryer without changing the total dryer system by adding a heating pipe into the drying chamber to produce better quality cocoa. From the results of simulations that have been carried out on the longitudinal axis alignment pipe design, the results of heat distribution are more evenly distributed than that of the widest axis directional pipeline arrangement. With the design of the longitudinal axis arrangement of the pipe, an estimated drying time of 7.9 hours is obtained, fuel consumption is between 0.15-0.28 m3 firewood, and there is no need for stirring during the drying process.Keywords: Cocoa, redesign, dryer, MATLAB.